2020
DOI: 10.25259/sni_600_2020
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery versus orthopedic surgery: Who has better access to minimally invasive spinal technology?

Abstract: Background: Our aim was to evaluate differences in neurosurgeons versus orthopedists access to technologies needed to perform minimally invasive spine surgeries (MISS) in Latin America. Methods: We sent a survey to members of AO Spine Latin America (January 2020), and assessed the following variables; nationality, level of hospital (primary, secondary, and tertiary), number of spinal operations performed per year, spinal pathologies addressed, the number of minimally invasive spine operations performed/yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, orthopedic surgeons were more likely to face problems related to hardware incompatibility and inexperience. In a survey of 306 spine surgeons in Latin America, Guiroy et al [ 31 ] did not find evidence of a difference in access to neuronavigation between orthopedic surgeons and neurosurgeons. However, Härtl et al [ 29 ] found that orthopedic surgeons were less likely to have access to neuronavigation (OR = 0.6; 95 % CI = 0.39–0.90; P = 0.02) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, orthopedic surgeons were more likely to face problems related to hardware incompatibility and inexperience. In a survey of 306 spine surgeons in Latin America, Guiroy et al [ 31 ] did not find evidence of a difference in access to neuronavigation between orthopedic surgeons and neurosurgeons. However, Härtl et al [ 29 ] found that orthopedic surgeons were less likely to have access to neuronavigation (OR = 0.6; 95 % CI = 0.39–0.90; P = 0.02) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Access to MISS in Latin America is difficult due to the implants costs, accessibility to surgical microscopes, and, more importantly, face-to-face educational opportunities in formal surgical teaching programs with a specialized «orthopedic and neurosurgical» approach are scarce. 3,4…”
Section: Miss Surgery Educationmentioning
confidence: 99%